Treatment of organized crime against civil servants in Mexico from the «criminal law of the enemy» perspective - Vázquez Pérez, Eduardo Daniel (2023)
The aim of this paper is to demonstrate the existence of the Enemy Criminal Law, by Professor Günther Jakobs, in the Mexican legislation structure and in international treaties to which the Mexican State is a party, in order to fight potentially dangerous subjects—enemies—who put at risk the balance of the social system with their actions. However, the applicability of this Law, at least in the Mexican case—which is of our interest—is not only directed to members of organized crime groups, but also to public servants who, during their term in office in the Public Administration and after leaving office, are connected with criminal organizations to perpetuate crimes that severely harm our society. Such assertions will be later demonstrated in detail in the following sections of this article. Finally, it is important to highlight that this article was drafted within the framework of a Doctorate in Organizations Intervention at Universidad Autónoma Metropolitana (UAM), Azcapotzalco Unit, Mexico City, Mexico.